The outcome of ICSI Cycles with Fresh Testicular Spermatozoa Obtained on the Day of or the Day before Oocyte Collection and with Cryopreserved Testicular Sperm in Patients with Azoospermia - Jan, Mir Abid; Keerio, Waqar Hussain; Khan, Khaiber; Bhurgri, Riaz Ahmed; Shaikh, Abdullah; Ali, Jamshid; Rehman, Khalil Ur (Journal of Neonatal Surgery, 2025)
Background: Infertility affects a significant proportion of couples worldwide, and male factor infertility accounts for approximately 40-50% of all cases. Objective: To evaluate the outcomes of Intracytoplasmic Sperm Injection (ICSI) cycles using fresh testicular spermatozoa obtained on the day of or the day before oocyte collection, compared to cycles utilizing cryopreserved testicular sperm, in patients with azoospermia. Methodology: This retrospective cohort study was conducted at Institute of Kidney Diseases, Hayatabad Medical Complex, Peshawar during December 2021 to May 2023. Data from 100 ICSI cycles were analyzed, with 50 cycles utilizing fresh testicular sperm and 50 cycles utilizing cryopreserved testicular sperm. Results: A total of 100 ICSI cycles were analysed, with no significant differences observed in male age (34.2 ± 5.1 years vs. 34.5 ± 5.2 years, p = 0.85), female age (31.4 ± 4.8 years vs. 31.1 ± 4.6 years, p = 0.79), type of azoospermia, or sperm retrieval method. In both groups, 56% (28/50) of patients had obstructive azoospermia, while 44% (22/50) had non-obstructive azoospermia in the fresh sperm group and 58% (29/50) and 42% (21/50) in the cryopreserved sperm group (p = 0.88). Sperm retrieval methods (TESE: 44% vs. 42%, micro-TESE: 56% vs. 58%) were also comparable (p = 0.79). Previous ART cycles were similar (1.3 ± 0.6 vs. 1.4 ± 0.7, p = 0.62), and the number of oocytes retrieved was identical (30 ± 5 in both groups, p = 0.96). Female BMI was also comparable (24.5 ± 3.3 kg/m² vs. 24.8 ± 3.4 kg/m², p = 0.76). Conclusion: It is concluded that fresh testicular sperm significantly improves the outcomes of ICSI cycles in men with azoospermia compared to cryopreserved testicular sperm. The study demonstrated higher fertilization rates, better embryo quality, and increased clinical pregnancy and live birth rates in the fresh sperm group.